FREQUENCY AND MORPHOLOGICAL PATTERNS OF CNS TUMORS IN A TERTIARY CARE HOSPITAL OF SOUTH PUNJAB - Qaisrani, Abdul Rehman; Shaheen, Uzma; Majeed, Sadia; Jahan, Naseem; Shaheen, Saba; Qaisrani, Farah Rehman (Pakistan Journal of Physiology, 2024)
Background: The incidence of CNS tumours is increasing rapidly especially in young population. CNS tumours include a set of neoplasms which originate form brain parenchyma, pituitary gland, pineal gland, spinal cord and meninges. The aim of this study was to observe the frequency and morphological patterns of CNS tumours in a tertiary care hospital of South Punjab. Methods: A cross-sectional descriptive study of 100 cases of brain tumours was conducted at the Pathology Department of DG Khan Medical College, Dera Ghazi Khan. One-hundred cases of CNS tumour biopsies were included with the relevant clinical and radiological findings. Results: A total of 100 cases of CNS tumours were studied. The morphological distribution of various CNS tumours was as follows: Astrocytoma (49%), Meningioma (19%), Schwannoma (8%), Oligodandroglioma (6%), Metastatic tumour (4%), Ependymoma (4%), Pituitary Adenoma (2%), Medulloblastoma (2%), Mixed Gliomas (2%), Germ Cell Tumours (1%), Craniopharyngioma (1%), Lymphoma (1%), Vascular tumours (1%). Conclusion: Among the CNS tumours Astrocytomas were the commonest tumours followed by Meningiomas, Schwannoma and Oligodendroglioma. Pak J Pathol 2024;20(2):24-6